The Application of Decision Tree C4.5 to Determine College Majors for Students After Madrasah Aliyah (Case Study: Madrasah Aliyah Misbahul Ulum) - Mulyani, Tasya; Bustami, Bustami (Department of Informatics, Universitas Malikussaleh, 2025)
This research aims (1) to implement the C4.5 Decision Tree in determining college majors for students after Madrasah Aliyah, (2) to assess the outcomes of applying the C4.5 Decision Tree method in selecting college majors for post-Madrasah Aliyah students, and (3) to design a decision support system that simplifies and speeds up the process of analyzing student data to determine suitable college majors. The system was developed using the PHP programming language, applying the C4.5 Decision Tree algorithm. Decision Tree is a machine learning algorithm that makes decisions using a set of rules structured like a tree. It employs conditional statements, with branches representing different decision-making steps aimed at producing optimal results. The process involves calculating entropy, split information, and gain ratio. This study, which focused on 12th-grade students during the odd semester, successfully identified appropriate engineering majors for each student.